2016
DOI: 10.1515/ijek-2016-0007
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Consumers’ Propensity for Online Shopping in a Developing Country: A Demographic Perspective

Abstract: The advent of the Internet continues to open new frontiers in digital marketing. One visible impact of the Internet in marketing has been the growing increase in online transactions which profits marketers and seemingly satisfies customers. However, in developing countries, the potential of online shopping has not been fully explored, and in some cases, are just non-existent. Lack of online infrastructure has often been attributed to the slower growth in online transactions in Africa, however, the customers’ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…Possible explanation for the nonrelevance of education in explaining shoppers' perception could be because of the increasing attention given to ICT education in both the Nigerian secondary and tertiary institutions. By contrast, Kwarteng and Pilik (2016) found that education had a significant relationship with shoppers' perceptions of retail convenience. Research findings have shown that online shoppers largely consist of people with higher level of education (Kehoe, Pitkow and Rogers, 1998;Hoffman, Kalsbeek and Novak, 1996).…”
Section: Discussion Of Findingsmentioning
confidence: 68%
“…Possible explanation for the nonrelevance of education in explaining shoppers' perception could be because of the increasing attention given to ICT education in both the Nigerian secondary and tertiary institutions. By contrast, Kwarteng and Pilik (2016) found that education had a significant relationship with shoppers' perceptions of retail convenience. Research findings have shown that online shoppers largely consist of people with higher level of education (Kehoe, Pitkow and Rogers, 1998;Hoffman, Kalsbeek and Novak, 1996).…”
Section: Discussion Of Findingsmentioning
confidence: 68%
“…Because of the dominance of studies conducted in the West in the literature, the majority of the research has overlooked some variables deemed essential in Africa, hence assuming that characteristics of African consumers are similar to those in the West or Asia (Kwarteng & Pilik, 2016). However, for example, electronic payment options that are commonly used in Western and Asian countries are still new and emerging in Africa and in need of extensive research to identify their impact on various stakeholders, including consumers (Kabir, Saidin, & Ahmi, 2015).…”
Section: Online Payment Options Awareness and Perception Of E-commerce And Propensity To Shop Onlinementioning
confidence: 99%
“…Statistics supplied by Business Tech (2015) showed that online shopping is practised through Europe, Oceania, South America, North America, and Africa. Oceania is the continent with the highest online shopping usage response rate, with New Zealand (95% participating consumers) that is the most active in this process (Kwarteng & Pilik, 2018). The highest usage in Europe has been identified in Finland (97% participating consumers).…”
Section: Online Shopping In Different Parts Of the Worldmentioning
confidence: 99%
“…Figure 2 displays this usage in more detail. On the African continent, Nigeria has the greatest online shopping activity followed by South Africa and Kenya (Kwarteng & Pilik, 2018). Among the BRICS nations (Brazil, Russia, India, China, and South Africa), SA lags behind Brazil, Russia and China in terms of online shopping transactions, with a 0.9 % purchase rate, followed by India with a 0.7% transaction rate.…”
Section: Online Shopping In Different Parts Of the Worldmentioning
confidence: 99%